Comparing the effect of peer-led versus adult-led AIDS education on knowledge, attitude and self-efficacy of female students in high schools in 4th region of education ministry in Tehran, using socio-cognitive theory, 2002-2003 - F Khalajabadi Farahani; F Ebadifar Azar (JRI, 2004)
Introduction: Iran is one of the Middle East countries involved in AIDS crisis. Around 17% of cases are between 20-29 years old and 35% between 30-39. Considering the long incubation period (around 10 years), obviously a great percentage of cases have become involved in their adolescent ages. To address this issue, school based AIDS educational program for adolescents is being considered as an important strategy of the ministry of education and the ministry of health in Islamic Republic of Iran. Accordingly, studying and recognition of the most effective method of education which leads to increasing knowledge, improvement of attitude and enhancement of life skills related to prevention of AIDS among adolescents seems to be a priority. This study was designed to compare the effects of two educational interventions for prevention of AIDS, conducted by peers and adults (school counselors), on knowledge, attitude and self efficacy of female students in high schools of Tehran, studying in human science field, in 4th region of ministry of education in 2002-3. The objective was to found new initiatives in school based AIDS educational programs. Materials and Methods: The mode of education used in this survey was Bendora Socio- Cognitive theory. A total of 441 students from 7 high schools in 4th region of ministry of education, were recruited using random cluster sampling and were allocated based on the educator, to 2 intervention groups (peer-led and adult-led group) and one control group. The educational subjects included AIDS prevention and correct attitudes towards AIDS (vulnerability and rejecting patients) and self-efficacy skills (decision making, problem solving and assertiveness). Anonymous questionnaires were filled by the students before and 30 days after the intervention. Data analysis was done using SPSS-11, and statistical tests including Analysis of variance, and Chi-Square were used. Results: The mean score of knowledge significantly increased in both interventional groups compared to control group after intervention (p<0.0001), but no significant difference was detected between peer-led and adult-led groups in this regard. Despite the equality between two interventional groups in the rise in knowledge, the type of information imparted by them was significantly different. Concerning the unique mode of education used in both groups, it seems that peer-led group more likely imparted those information which were a matter of concern among their peers and friends (e.g. transmission mode) while adults (school counselors) imparted some other informations (e.g. treatment, vaccination). There was no significant improvement in the attitude of vulnerability towards AIDS among interventional groups from pre-intervention to post-intervention. Whereas the attitude of rejecting AIDS patients in both interventional groups has improved compared to control group (p<0.0001), no difference has been detected between the two interventional groups in this regard. The educational intervention only in adult-led group has led to enhancement of self-efficacy skills significantly compared to control group, from pretest to posttest, however, there was no significant difference between peer –led and adult-led group in this issue. Conclusion: we recommend both peer-led and adult- led programs to be employed in school-based AIDS education, particularly peers in imparting information according to their peer’s need and adults in training self efficacy skills. However further studies with larger sample size and longer educational periods are recommended to confirm the current results.
Keywords: AIDS, Prevention, Knowledge, Education, Attitude, Self-efficacy, Peers, Socio-cognitive theory, Adolescent